A high cholecystectomy rate in a cohort of women who are Mexican-American, and postpartum, at the time of oral contraceptive pill initiation - Stuart, Gretchen S. (2007)
BACKGROUND: Opinions differ regarding the association between gallbladder disease and oral contraceptive (OCs). The objective of this paper is to quantify cholecystectomy rate among women initiating OCs. STUDY DESIGN: Women under age 25 years were enrolled at four sites in a randomized trial evaluating initiation of OCs. Hospitalizations while enrolled were elicited during follow-up interviews, and medical records of women who underwent cholecystectomy were reviewed. RESULTS: Eight of 757 women enrolled at University of Texas Southwestern Medical Center (UTSW) underwent cholecystectomy, a rate of 25.3/1000 woman-years (95% CI 8.1, 42.5). All eight were Mexican-American and postpartum when they initiated OCs. The expected rate is 4.2/1000 woman-years for US women aged 15–44. CONCLUSIONS: Women enrolled at the UTSW site had an increased rate of cholecystectomy, and were more likely to be postpartum and Mexican-American than women enrolled at the other sites.